2010
DOI: 10.1007/s00063-010-1060-4
|View full text |Cite
|
Sign up to set email alerts
|

Krankheitskosten bei Alzheimer-Demenz

Abstract: The results demonstrate that non-antidementive therapy for Alzheimer's disease causes higher costs especially in nursing care. The memantine group proved superior even though it had the highest costs in the specific drug category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Based on previous studies, we expected a different degree of ADL dependency for individuals in each setting [12,17,18] and regarded an unequal care level distribution as a potential source of bias. For a comprehensive comparison, we therefore further stratified both populations according to care level, using the care level assigned on 30 June as the classification criterion.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous studies, we expected a different degree of ADL dependency for individuals in each setting [12,17,18] and regarded an unequal care level distribution as a potential source of bias. For a comprehensive comparison, we therefore further stratified both populations according to care level, using the care level assigned on 30 June as the classification criterion.…”
Section: Methodsmentioning
confidence: 99%
“…8 Studies with data from statutory health insurance calculated dementia-related costs to range between €586 and €1129 per month. 9,10 Other European studies found that total costs were between €507 and €2411 (mild) and €881 and €4579 (severe). 5,8 A recent study on the determinants of the societal costs (total costs for the society) of DAT listed the cost predictors from several studies, 11 to which we added the latest references (see Table S1 in supporting information).…”
Section: Introductionmentioning
confidence: 99%
“…For patients in long‐term care institutions, the costs were even higher, ranging from €5109 (mild) to €5311 (severe) 8 . Studies with data from statutory health insurance calculated dementia‐related costs to range between €586 and €1129 per month 9,10 . Other European studies found that total costs were between €507 and €2411 (mild) and €881 and €4579 (severe) 5,8 …”
Section: Introductionmentioning
confidence: 99%
“…Die Ergebnisse zeigen, dass Verzicht auf Antidementiva besonders in der Pflege mit höheren Kosten verbunden ist. Die niedrigsten Kosten finden sich trotz relativ hoher Arzneimittelkosten in der Gruppe, die medikamentös behandelt wurde [33]. Eine Beschränkung auf die Kostenträgerperspektive GKV greift hier definitiv zu kurz.…”
Section: Integrationsaspekte: Vermeidung Von Pflegekosten Bei Alzheimunclassified